Due to the Gloomy Economic Outlook EU Fight against Tax Havens Enters a New Phase - Narciz BĂLĂȘOIU (Revista de Management Comparat International, 2021)
An important part of the massive loss of income registered by some states of the European Union is due to the tax havens. It is estimated that last year alone the impact at EU level was 75 billion Euros. Fiscal losses are equivalent to almost 52% of the combined public health budgets of poor countries and respectively 8% for rich countries. These data have generated increasing public pressure, which has led to a more pragmatic involvement of decision makers. Due to the Covid-19 crisis, the situation is becoming imperative, as the amounts needed to cover spending on health and social services have increased significantly. The EU created a list of tax havens in 2017 based on a definition of harmful tax practices in order to counter the practices of large companies that avoid paying their tax obligations by using the subterfuges offered by tax havens. The strategy was to put pressure on countries that allow this practice, encouraging blacklisted countries to change their tax rules.